Handbook of Quality of Life in African Societies - Eloff, Irma.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This handbook reflects on quality-of-life in societies on the continent of Africa. It provides a widely interdisciplinary text with insights on quality-of-life from a variety of scientific perspectives. The handbook is structured into sections covering themes of social context, culture and community; the environment and technology; health; education; and family. It is aimed at scholars who are working towards sustainable development at the intersections of multiple scientific fields and it provides measures of both objective and subjective quality-of-life. The scholarly contributions in the text are based on original research and it spans fields of research such as cultures of positivity, wellbeing, literacy and multilinguism, digital and mobile technologies, economic growth, food and nutrition, health promotion, community development, teacher education and family life. Some chapters take a broad approach and report on research findings involving thousands, and in one case millions, ofparticipants. Other chapters zoom in and illustrate the importance of specificity in quality-of-life studies. Collectively, the handbook illuminates the particularity of quality-of-life in Africa, the unique contextual challenges and the resourcefulness with which challenges are being mediated. This handbook provides empirically grounded conceptualizations about life in Africa that also encapsulate the dynamic, ingenious ways in which we, as Africans, enhance our quality-of-life. .
Preface: Quality of Life in African Societies; Valerie Møller -- Part I. Social Context, Culture and Community -- 1. Cultures of Positivity: Interconnectedness as a Way of Being: Marié P. Wissing, Lusilda Schutte and Angelina Wilson Fadiji -- 2. Communities in Action: The Participation of Communities in two South African Literacy Campaigns; Veronica McKay -- 3. The Development of an Integrated, Multi-level Process to Facilitate the Promotion of Holistic Wellbeing in School Communities; Ansie Elizabeth Kitching -- 4. Wellbeing as Positive Outcome of a Social Connectedness Pathway to Resilience: An Indigenous Psychology Perspective; Janna de Gouveia and Liesel Ebersöhn -- 5. Adolescent Resilience in the Face of Relentless Adversity: The Role of Strong, Black Women; Linda C. Theron and Michael Ungar -- 6. Conversations as Carriers of Meaning to a Common Good; Helena Á. Marujo, Luis M. Neto and Marié Wissing -- Part II. Environment and Technology -- 7. Economic Growth and Quality of Life in Africa; Carolyn Chisadza and Elsabé Loots -- 8. Improving Health Outcomes and Quality of Life for African Adolescents: The Role of Digital and Mobile Games; Tyra M. Pendergrass, Kimberly Hieftje and Lynn E. Fiellin -- Part III. Health -- 9. Research, Innovation and Education Towards Malaria Elimination: Improving Quality of Life in Africa; Christiaan de Jager, Taneshka Kruger and Cheryl Tosh -- 10. How Prioritised Policy Commitment has Improved Food Security and Nutrition in Africa; Nokuthula Vilakazi and Sheryl L. Hendriks -- 11. Changing Trends in the Provision of Psychosocial and Health Resources for Quality Childhood Development in Cameroon; Therese Mungah Shalo Tchombe Cameroon -- 12. Humanizing Silence: The Representation of HIV & AIDS in South African Narratives; Vasu Reddy -- 13. The Use of Support Groups to Facilitate Resilience and Quality of Life in Families Affected by HIV; Michelle Finestone -- 14. Decolonial Approaches to AIDS, Children's Wellbeing, and Education in Malawi; Zikani Kaunda, Nancy Kendall and Upenyu Majee -- Part IV. Education -- 15. An EI Approach to Parent Communication amongst In-Service Teachers; Giulietta Domenica Harrison -- 16. Quality of Life through Capacity Development in Junior Primary Teacher Education; Charmaine Villet and Jan Weiss -- 17. Developing Capacity for Teacher Inservice Education in Rural Tanzania: Embracing Emergent Phenomena; Elaine Simmt, Andrew Binde, Florence Glanfield and Joyce Mgombelo -- 18. Improving Quality of Life through Teaching and Learning Innovations in Multilingual Contexts: Lessons from Sub-Saharan Africa; Funke Omidire -- 19. The Quality of Life of Teachers in Sudan; Amani Ibrahim Abedelgafar -- Part V. Family -- 20. Traditional Views of Black South Africans on Quality and Successful Family Life; Ruth Mampane, Selogadi Ngwanagwato Mampane and Sylvia Ocansey -- 21. "Whatever Small Thing I have, I Should Be Grateful For": Gratitude as Understood and Experienced by Black South African Adolescents; Tharina Guse and Tshiamo T. Matabane -- 22. Researching Children's Subjective Well-Being in South Africa: Considerations for Method, Theory and Social Policy; Shazly Savahl, Sabirah Adams, Elizabeth Benninger, Maria Florence, Kyle Jackson, Donnay Manual, Mulalo Mpilo and Umesh Bawa -- 23. An Outsider in South Africa: Critical Reflections on Ubuntu; Sheila Trahar -- 24. Narratives of Quality of Life in Africa: A Kaleidoscope of Hope; Irma Eloff. .
Keywords: Quality of life; Positive psychology; Educational psychology; Quality of Life Research; Positive Psychology; Educational Psychology